Probing conformational states of glutaryl-CoA dehydrogenase by fragment screening - Begley, Darren W. (International Union of Crystallography, 2011)
Glutaric acidemia type 1 is an inherited metabolic disorder which can cause macrocephaly, muscular rigidity, spastic paralysis and other progressive movement disorders in humans. The defects in glutaryl-CoA dehydrogenase (GCDH) associated with this disease are thought to increase holoenzyme instability and reduce cofactor binding. Here, the first structural analysis of a GCDH enzyme in the absence of the cofactor flavin adenine dinucleotide (FAD) is reported. The apo structure of GCDH from Burkholderia pseudomallei reveals a loss of secondary structure and increased disorder in the FAD-binding pocket relative to the ternary complex of the highly homologous human GCDH. After conducting a fragment-based screen, four small molecules were identified which bind to GCDH from B. pseudomallei. Complex structures were determined for these fragments, which cause backbone and side-chain perturbations to key active-site residues. Structural insights from this investigation highlight differences from apo GCDH and the utility of small-molecular fragments as chemical probes for capturing alternative conformational states of preformed protein crystals.